Anisotropic nonlinear elliptic systems with variable exponents and degenerate coercivity. Issue 11 (18th August 2021) - Mokhtar, Naceri; Mokhtari, Fares
Abstract: In this paper, we prove existence results for distributional solutions of anisotropic nonlinear elliptic systems with variable growth and degenerate coercivity. The functional setting involves anisotropic Sobolev spaces with variable exponents as well as weak Lebesgue (Marcinkiewicz) spaces with variable exponents.